KEPASTIAN HUKUM TERHADAP PERJANJIAN KERJA BERSAMA DALAM PERSPEKTIF HUKUM KETENAGAKERJAAN - Sarikin, Sarikin; Hedwig Adianto Mau; Nur Hakim (Bajang Institute, 2025)
In the field of labor, disputes between employers and workers usually arise because of feelings of dissatisfaction. Employers provide policies that they consider good and will be accepted by workers, but because the workers concerned have different considerations and views. However, in its implementation, there are various challenges in aligning the interests of employers and workers, especially in the context of the Collective Labor Agreement and the Law. From this background, the formulation of the problem arises, namely 1) How does Law Number 6 of 2023 affect the validity and implementation of the Collective Labor Agreement (PKB)? 2) What are the prospects and challenges of implementing the Collective Labor Agreement (PKB) in industrial relations in the future after the enactment of Law Number 6 of 2023? This study uses the theory of agreement and the theory of legal certainty. This research is descriptive with a normative legal approach emphasizing the use of secondary data in positive legal principles, namely laws and regulations and library materials with qualitative data analysis techniques. The results of this study show that the implementation of the PKB in the future is greatly influenced by how all parties, both workers, employers, and the government are able to understand and adapt to the dynamics of the new labor law. Law No. 6 of 2023, although it has pros and cons, must still be used as a legal reference in compiling a balanced and fair PKB. Therefore, the success of the implementation of the PKB in the future requires collective efforts from all parties: workers, employers, and the government. There needs to be a shared awareness that the PKB is a product of social dialogue that must be built on a foundation of trust, legal knowledge, and a willingness to work together.